Improving the quality of care of respiratory syncytial virus in the neonatal and pediatric populations globally - Jah, Fungwe; Mejias, Asuncion; Nzirawa, Tendai; Silveira, Rita C.; Berger, Angelika; Travan, Laura; Kinoshita, Daisuke; Ishak, Shareena; Çelik, Tolga; Al-dandan, Faisal; Mahr, Benedikt; Masters, Christine (Frontiers in Pediatrics, 2025)
Respiratory syncytial virus (RSV) is the leading cause of hospitalization for bronchiolitis in infants worldwide, and age (<6 months) and underlying comorbidities (e.g., prematurity, congenital heart disease) are risk factors for severe disease. However, some centers face challenges in identifying and implementing preventative measures, and best practices, for the care of at-risk infants. Therefore, this study aimed to identify best practice examples in RSV care for neonatal and pediatric populations in leading centers globally, and to understand how these practices can be widely implemented. Following a literature review, multidisciplinary teams were interviewed in 10 centers globally (1 center per country; 40 interviews conducted between May and November 2023). Centers were included based on pre-determined criteria (e.g., type of center, services provided, focus on RSV research) to ensure a representative view of RSV care. The identified best practice interventions were critically reviewed by a group of RSV experts [healthcare professionals (HCPs) and a patient group representative] and assessed for their impact on patient care and transferability to other centers. Fifty-seven unique best practice interventions were identified, sixteen of which were prioritized, across five best practice themes: (1). Caregiver education and engagement: Provision of timely caregiver education on RSV infection and care. (2). HCP education: Provision of continuous evidence-based HCP education. (3). HCP-led RSV prophylaxis services: Additional support services to ensure at-risk infants are protected ahead of the RSV season. (4). Protocols and ways of working: Establishing evidence-based procedures to ensure best practices are followed within clinical practice. (5). Technology and innovation: Leveraging digital services to optimize care delivery and experience. This study identified interventions that may improve patient outcomes and quality of care for RSV disease in the pediatric and neonatal populations. The next steps will be to disseminate and implement best practice examples across healthcare systems and care settings globally.